Proportion of cervical excision for cervical intraepithelial neoplasia as a predictor of pregnancy outcomes. Issue 2 (2nd October 2014) - Kyrgiou, Maria; Valasoulis, George; Stasinou, Sofia‐Melina; Founta, Christina; Athanasiou, Antonios; Bennett, Phillip; Paraskevadis, Evangelos
Abstract: Objective: To assess how the proportion of the cervical volume/length removed during treatment for cervical intraepithelial neoplasia (CIN) varies and whether this correlates to the pregnancy duration at delivery. Methods: The present prospective observational study included 142 women undergoing CIN treatment at a university hospital during 2009–2013. The pretreatment and post‐treatment cervical dimensions and cone size were measured with magnetic resonance imaging, three‐dimensional transvaginal ultrasonography, or two‐dimensional transvaginal ultrasonography, and the correlation between pregnancy outcomes and the relative proportion of the cervix excised was assessed. Results: Pretreatment cervical volumes and cone volumes varied substantially (range 11–40 cm 3 and 0.6–8 cm 3, respectively). The proportion of the volume excised ranged from 2.2% to 39.4%. Sixteen (11%) women conceived following treatment; 12 had a live birth (seven at term, three preterm). The pregnancy duration at delivery was significantly correlated with the proportion of the cervical volume ( r = −0.9; P < 0.001) and length ( r = −0.7; P = 0.01) excised and the cone volume ( r = −0.6; P = 0.04). Conclusion: The pretreatment cervical dimensions and the proportions of the volume/length excised vary substantially, and the latter correlates with the pregnancy duration. Assessment of the proportion excised might help to stratify women at risk who need intensive surveillance when pregnant.